Impact of gender-biased parental perceptions on under-immunization in Eastern Sudan: a cross-sectional study - Abdallah, Malaz Sulieman; Jumma, Taqwa; Elhadi, Yasir Ahmed Mohammed; Sabahelzain, Majdi M. (Frontiers in Global Women's Health, 2024)
BackgroundDespite global efforts, inequities in vaccine uptake remain, influenced by socioeconomic, geographic, cultural, and gender-related factors. In Eastern Sudan, gender disparities are acknowledged, particularly in livelihoods, but their impact on vaccination uptake is unclear. This study aimed to assess the effect of gender-biased parental perceptions on under-immunization among children in Kassala, Eastern Sudan.MethodsThis study was a community-based cross-sectional in rural and urban districts of Kassala locality in Kassala State, Eastern Sudan in November 2022. Data were collected from parents using a pre-tested, structured questionnaire. The Chi-square or Fisher's exact test was conducted to assess the factors associated with under-immunization among children.ResultsData were collected from 400 parents. Our data reveal that most children were fully vaccinated with the three doses of the pentavalent vaccine (83%), while 14% were partially vaccinated. Findings showed that about one in five parents perceived male vaccination as more important than female vaccination. This parental perception of gender-based importance in vaccination was significantly associated with under-immunization among children (p-value = 0.049). Additionally, males in our study are fully vaccinated 5% more often than females. Socio-economic factors, including mothers’ education and households’ income level, were also significantly associated with the vaccination status of the children.ConclusionThis study shed light on the effect of gender norms and related determinants on equitable access to vaccinations for boys and girls alike. More research is needed to gain a better understanding of the gender norms related to vaccination and their long-term impact on immunization demand and resilience in this region.